Service learning: a study of administrators' goals at a Research I university - Sanders, Christy (2002)
This case study explored the administrators' goals of a service learning program at a Research I university. This research was aimed at discovering administrators' goals and determining whether or not these goals were achieved, as perceived by students, administrators, community service agency directors, and faculty members. A structured, tape-recorded interview was used to gather data from participants in all groups. Barriers to implementation of service learning by faculty, students, and administrators included time constraints, lack of institutional support and lack of clarity as to what constituted service learning. University engagement in service learning was defined as the process by which a university embraces service learning wholeheartedly. The engagement may take place through redesigned curriculum and teaching methodology. This study's findings reveal that administrators' goals related to university engagement in service learning. Furthermore, the administrators' goals showed that the students were supplementing their academic experience with service to the community. This dissertation suggests that service learning can be mutually beneficial to all partners. Further, for a service learning program to flourish, all participants must have a role in defining its goals and clarifying its purposes